2018
DOI: 10.4103/sni.sni_171_18
|View full text |Cite
|
Sign up to set email alerts
|

Cervical C2 to C4 schwannoma with intratumoral hemorrhage presenting as acute spastic quadriparesis: A rare case report

Abstract: Background:Spinal schwannomas are slow growing, benign nerve sheath tumors. These may be asymptomatic or may present as backache with radicular pain, slowly progressive neurological deficits, but rarely with acute spastic quadriparesis attributed to intratumoral hemorrhage.Case Description:A 38-year-old male presented with the chief complaint of neck pain radiating to the left upper extremity for the last 8 months. On admission, he exhibited diffuse hyper-reflexia but had no motor or sensory deficit. Magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In our literature review, urgent tumor resection was performed as observed in nine reports [1,2,7,[10][11][12][13][14][15], elective surgery reported by two [4,16], with no record in another two [8,17] (Table 1). Complete recovery was achieved in five of nine patients who underwent urgent surgery, whereas four had neurological sequelae, such as ambulation with aid, no improvement in BBD and quadriplegia with respiratory paralysis [1,4,10].…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, urgent tumor resection was performed as observed in nine reports [1,2,7,[10][11][12][13][14][15], elective surgery reported by two [4,16], with no record in another two [8,17] (Table 1). Complete recovery was achieved in five of nine patients who underwent urgent surgery, whereas four had neurological sequelae, such as ambulation with aid, no improvement in BBD and quadriplegia with respiratory paralysis [1,4,10].…”
Section: Discussionmentioning
confidence: 99%
“…[ Table 1 ]. [ 3 , 4 , 9 ] Patients presented with quadriparetic neurological deficits, variably accompanied by sensory and/ or sphincteric changes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 10 ] Patients with acute intratumoral hemorrhages into cervical schwannomas may present with the rapid onset of pain, radiculopathy, and/or myelopathy warranting urgent/emergent resection and stabilization. [ 2 - 4 , 6 , 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…These hemorrhagic lesions affect almost equally the cervical spine (24%), 4 , 5 , 8 , 11 , 18 , 25 , 27) the lumbar tract (24%), 7 , 13 , 16 , 17 , 21 , 22 , 28) the thoracic tract (20%), 2 , 6 , 9 , 14 , 19 , 29) and the thoraco-lumbar passage (20%) 10 , 12 , 20 , 22 , 24 , 26) while the thoraco-cervical, 15) the sacral-lumbar tract, 30) and the sacral spine 23) are more rarely involved (12%). Bleeding can occur within the tumor (34%), 6 , 11 , 12 , 17 , 22 , 25 , 26 , 27 , 28 , 30) between the inner layer of the dura mater and the arachnoid mater of the meninges (subdural hematoma: 22%) 4 , 5 , 8 , 9 , 16 , 18 , 19) or into the subarachnoid space (subarachnoid hemorrhage: 16%) 7 , 10 , 20 , 21 , 24) ; multiple sites can also be involved (13%), such as intratumoral bleeding with subdural hematoma 2 , 23 , 29) or subarachnoid hemorrhage. 13) …”
Section: Discussionmentioning
confidence: 99%